Ascending Aortic Injuries Following Blunt Trauma. Issue 6 (November 2013) - Sun, Xiumei; Hong, Jenny; Lowery, Robert; Goldstein, Steven; Wang, Zuyue; Lindsay, Joseph; Hill, Peter C.; Corso, Paul J.
Abstract Background The diagnosis and the management of traumatic thoracic aortic injuries have undergone significant changes due to new technology and improved prehospital care. Most of the discussions have focused on descending aortic injuries. In this review, we discuss the recent management of ascending aortic injuries. Methods We found 5 cohort studies on traumatic aortic injuries and 11 case reports describing ascending aortic injuries between 1998 to the present through Medline research. Results Among case reports, 78.9% of cases were caused by motor vehicle accidents (MVA). 42.1% of patients underwent emergent open repair and the operative mortality was 12.5%. 36.8% underwent delayed repair. Associated injuries occurred in 84.2% of patients. Aortic valve injury was concurrent in 26.3% of patients. The incidence of ascending aortic injury ranged 1.9–20% in cohort studies. Conclusions Traumatic injuries to the ascending aorta are relatively uncommon among survivors following blunt trauma. Aortography has been replaced by computed tomography and echocardiography as a diagnostic tool. Open repair, either emergent or delayed, remains the treatment of choice. doi: 10.1111/jocs.12237 (J Card Surg 2013;28:749–755)